2005
DOI: 10.1002/mas.20059
|View full text |Cite
|
Sign up to set email alerts
|

Applications of accelerator mass spectrometry for pharmacological and toxicological research

Abstract: The technique of accelerator mass spectrometry (AMS), known for radiocarbon dating of archeological specimens, has revolutionized high-sensitivity isotope detection in pharmacology and toxicology by allowing the direct determination of the amount of isotope in a sample rather than measuring its decay. It can quantify many isotopes, including 26Al, 14C, 41Ca, and 3H with detection down to attomole (10(-18)) amounts. Pharmacokinetic data in humans have been achieved with ultra-low levels of radiolabel. One of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 95 publications
0
66
0
Order By: Relevance
“…Only one recent study reported mass spectrometric identification and structural confirmation of an adduct between PhIP and a model albumin peptide encompassing the reactive Cys34 residue (Chepanoske et al, 2004). Due to the very low environmentally relevant doses of these heterocyclic amines, sensitivity in animal and human studies is often a limiting factor: therefore a sophisticated attomole-sensitivity technique, accelerator mass spectrometry (Brown, Tompkins, & White, 2006) has been employed to measure DNA-and protein-heterocyclic amine adducts (Dingley et al, 1998;Turteltaub et al, 1999).…”
Section: Food Lifestyle and Indoor Air Carcinogensmentioning
confidence: 97%
“…Only one recent study reported mass spectrometric identification and structural confirmation of an adduct between PhIP and a model albumin peptide encompassing the reactive Cys34 residue (Chepanoske et al, 2004). Due to the very low environmentally relevant doses of these heterocyclic amines, sensitivity in animal and human studies is often a limiting factor: therefore a sophisticated attomole-sensitivity technique, accelerator mass spectrometry (Brown, Tompkins, & White, 2006) has been employed to measure DNA-and protein-heterocyclic amine adducts (Dingley et al, 1998;Turteltaub et al, 1999).…”
Section: Food Lifestyle and Indoor Air Carcinogensmentioning
confidence: 97%
“…14 C]-labelled resveratrol and accelerator mass spectrometry [35] to elucidate the full plasma pharmacokinetic profile of a dietary attainable dose of resveratrol in healthy volunteers as well as measuring prostate and colorectal tissue concentrations in patients undergoing surgery.…”
Section: High Dose Versus Dietary Dosementioning
confidence: 99%
“…Advances in HPLC technology (e.g., ultra high performance liquid chromatography or UHPLC) also have contributed to the greatly enhanced capabilities of contemporary LC-MS/MS systems, not only in terms of chromatographic resolution and associated speed of separations, but also with regard to the capacity and robustness afforded by the current generation of columns, autosamplers, pumping systems, and so forth. Accelerator mass spectrometry (AMS), a technique employed originally for applications in the geophysical sciences, has been developed as an exquisitely sensitive tool for biomedical applications, including studies of drug disposition, in which trace amounts of a radioisotope (e.g., 14 C) can be detected and quantified in blood or excreta following the administration of a microdose of the agent of interest (30). In the area of therapeutic proteins and monoclonal antibodies, matrix-assisted laser desorption-ionization (MALDI) mass spectrometry has become an important technique (in addition to ESI) not only for qualitative applications but also as a reference method against which immunological assays (e.g., ELISA) can be validated for determining the PK properties of these biologics in animals and humans (31).…”
Section: The Past 20 Yearsmentioning
confidence: 99%